Path analysis of the awareness status and influencing factors of sarcopenia in older adults in the community: based on structural equation modeling - Wang, Dahui; Zeng, Huaying; Wu, Peiwen; Zhou, Yuchen; Chen, Hongkun; Zhao, Falin; Liu, Shucong (Frontiers in Public Health, 2024)
Background Sarcopenia is a progressive geriatric syndrome that impacts older adults’ quality of life. Insufficient focus has been given to sarcopenia among Chinese residents, resulting in low level of sarcopenia awareness. This study aims to investigate awareness of sarcopenia and its influencing factors and the influencing pathways among older adults in Hangzhou. Methods A stratified random sample of 942 community-dwelling older adults was evaluated using the SARC-CalF screening tool, along with a questionnaire based on health ecology theory to assess awareness of sarcopenia and its influencing factors and the influencing pathways. Descriptive statistics, linear regression analysis, and path analysis were conducted using SPSS 25.0 and Amos 23.0 to analyze the data. Results The mean awareness score for sarcopenia was 60.26 ± 7.31. Self-rated physical health, daily intake of high-quality protein, exercise frequency, smoking status, self-efficacy, religious beliefs, social support, education level, occupation, participation in community free medical examinations, and awareness of nutrition policy were all factors affecting scores for sarcopenia awareness (p < 0.05). Except for negative effects observed in social support, smoking status, and self-rated physical health, all others exhibit positive effects. Conclusion Community healthcare institutions should target populations with low awareness of sarcopenia and focus on these key factors. Diverse health education programs and multi-channel screening activities can promote awareness, guide healthy lifestyles and prevent or delay the onset of sarcopenia in the older.